Evaluación de seguridad y riesgos laborales del área de pintura en la empresa ciauto bajo normas gtc 45. - Medina Arcos, Lenin Ricardo (2019)
This research project has as a result the evaluation of occupational safety and risks through the GTC-45 guide within the paint plant in the CIAUTO’S company, since previously there had not been an assessment of this sector of the organization, the object of this study is to identify the dangers within the area and minimize the impact of incidence that may have on the employees who work in it. All the elements, routine activities and processes that make up the Painting area were analyzed as factors of great relevance. Through the recognition of risks, they help to make the risk of an acceptable nature when carrying out any work activity. During the development of the research, the painting area of the company "CIAUTO", dedicated to the assembly of Great Wall vehicles imported from China, was taken into account.The GTC 45 is a Colombian guide regulated by the ICONTEC (Colombian Institute of technical standards and Certification) that serves as an entity that identifies the dangers and the assessment of occupational health and safety risks, whose primary objective is to establish standards that benefit to employees when they are working in their different jobs. We used field research, bibliography, surveys, which resulted in risks: physical, chemical, ergonomic and electrical. For the following it was determined that the greatest danger is the physical one that is of improvable character, meanwhile the others have a character of acceptable, it is should be mentionated that this guide is a management system applicable in any company that wishes to create a preventive culture within each one and requirements that help to comply with established norms of each country that help to the prevention and minimization of accidents.